2020
DOI: 10.1136/bmjsem-2019-000668
|View full text |Cite
|
Sign up to set email alerts
|

Cycling but not walking to work or study is associated with physical fitness, body composition and clustered cardiometabolic risk in young men

Abstract: IntroductionActive commuting is an inexpensive and accessible form of physical activity and may be beneficial to health. The aim of this study was to investigate the association of active commuting and its subcomponents, cycling and walking, with cardiometabolic risk factors, physical fitness and body composition in young men.MethodsParticipants were 776 Finnish young (26±7 years), healthy adult men. Active commuting was measured with self-report. Waist circumference was measured and body mass index (BMI) calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
5
1
1
Order By: Relevance
“…The most recent NHANES analysis of AT trends in the U.S. reported that 14% of adults exceeded 150 min/wk of AT, whereas our study found that 31% and 33% met this criterion by accelerometer/GPS or self-report, respectively [25]. In two studies that similarly assessed AT trips for any purpose, not just for commuting, one-quarter of the sample self-reported some amount of AT, compared to 66% in the current study [27,71]. Though we aimed to maximize variability in walkability surrounding participants' home location, recruiting from urban block groups have led to the selection of a more active sample than the general population and limited our ability to detect small associations with CVD outcomes.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The most recent NHANES analysis of AT trends in the U.S. reported that 14% of adults exceeded 150 min/wk of AT, whereas our study found that 31% and 33% met this criterion by accelerometer/GPS or self-report, respectively [25]. In two studies that similarly assessed AT trips for any purpose, not just for commuting, one-quarter of the sample self-reported some amount of AT, compared to 66% in the current study [27,71]. Though we aimed to maximize variability in walkability surrounding participants' home location, recruiting from urban block groups have led to the selection of a more active sample than the general population and limited our ability to detect small associations with CVD outcomes.…”
Section: Discussioncontrasting
confidence: 81%
“…The blood pressure multivariate models included statins and antihypertensive medications and the glucose models adjusted for insulin, metformin, or glucose-lowering medications. Our final models did not adjust for BMI as it may mediate the relationship between AT and CVD risk factors [ 27 , 31 ], though we compared to models with BMI adjustment to explore this relationship. As 96% of the population had access to a vehicle, we did not include vehicle access in the models, but we did describe differences in device-assessed and self-reported AT by this variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of physical activity can be easily integrated into everyday life, particularly for those not interested in engaging in other kinds of activities such as sports, training in gyms, etc. [18]. Increasing active transportation is a crucial population-based strategy, which aims to reverse the burden of CVD through decreasing physical inactivity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Active transportation has been demonstrated to be an excellent strategy for increasing physical activity level, because it is a daily behavior, an opportunity to create a healthy habit and relatively cheap alternative [ 10 , 11 ]. Besides, it can be integrated into everyday life particularly for those not involved or interested in engaging in leisure time physical activity [ 12 ]. Strong evidence demonstrates that physical activity related to active transportation is a crucial population-based approach, which aims to reverse the health outcomes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%